VALUE OF CULTURE IN THE PEOPLE'S STORY OF LAMAHOLOT, EAST FLORES DISTRICT (CONTENT ANALYSIS) - Jakobis Tallo Adu; Yumna Rasyid; Zuriyati Zuriyati (Universitas Indraprasta PGRI, 2019)
Abstrack. The world of literature is an imaginative world that describes human life, which we can enjoy, understand and contemplate. Life in society that we can find is cultural value. The purpose of this research is to find out the cultural values in the Lamaholot folklore of East Flores Regency. This study uses a qualitative approach that uses words as data to convey research results. The research method used to analyze this folklore is the content analysis method. Cultural values include: cultural values in human relations with God, cultural values in human works, cultural values in human relations with nature, and cultural values in human relations with others. Descriptive research techniques conducted by researchers are techniques examining elements of cultural values. This research technique can be done by reading carefully to find cultural values, identify, classify, analyze, and conclude research data about the cultural values in the story. From the results of the study found 99 quotes related to the four cultural values studied. Keywords : cultural values, folklore, and content analysis